2019
DOI: 10.2134/cftm2019.03.0018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Rate and Timing, Fungicide Application Method, and Simulated Rainfall after Fungicide Application on Brown Patch Severity in Tall Fescue

Abstract: Tall fescue lawns can be fertilized during the summer months at modest N rates without affecting brown patch severity.• When an appropriate fungicide such as Heritage was used for brown patch management, the method of fungicide delivery did not affect brown patch suppression.• Simulated rainfall up to 0.5 inches within 15 min of fungicide application did not compromise fungicide efficacy. AbstractIn North Carolina, tall fescue (Festuca arundinacea Schreb.) is widely grown throughout the Mountain and Piedmont r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Higher rates of annual N were found to increase brown patch severity compared to unfertilized TTTF or lower rates of N (Burpee, 1995;Cutulle et al, 2014;Watkins & Wit, 1993). However, other studies reported that annual N rates (<294 kg N ha −1 ) throughout the growing season did not affect brown patch severity in Coronado TTTF (Butler et al, 2019;Teuton et al, 2007). Currently, best management practices for N fertility with regard to management of brown patch among all cool-season species are to avoid an abundance of quick-release N sources and prevent insufficient N to avoid enhancing disease severity (Tredway et al, 2023).…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher rates of annual N were found to increase brown patch severity compared to unfertilized TTTF or lower rates of N (Burpee, 1995;Cutulle et al, 2014;Watkins & Wit, 1993). However, other studies reported that annual N rates (<294 kg N ha −1 ) throughout the growing season did not affect brown patch severity in Coronado TTTF (Butler et al, 2019;Teuton et al, 2007). Currently, best management practices for N fertility with regard to management of brown patch among all cool-season species are to avoid an abundance of quick-release N sources and prevent insufficient N to avoid enhancing disease severity (Tredway et al, 2023).…”
Section: Core Ideasmentioning
confidence: 99%
“…Future studies focused on quantification of potential reductions in fungicide requirements to manage brown patch could further demonstrate sustainable approaches for turfgrass disease management. Previous research evaluating the relationship between N fertilization and brown patch severity has only compared responses within an individual species (Bloom & Couch, 1960;Burpee, 1995;Butler et al, 2019;Fidanza & Dernoeden, 1996a;Watkins & Wit, 1993). Traditional management recommendations have been to limit or avoid N applications during the spring and summer to avoid enhancing brown patch severity across all cool-season turfgrass species (Couch, 1995;Tredway et al, 2023;Watschke et al, 2013).…”
Section: Crop Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…It was rapidly adopted and has become prolific even in areas not intentionally sown because of seed dispersal by birds, machinery, etc. It has a clumping growth structure from production of short rhizomes and abundant tillers over time, although with dense seed placement forms a thick sod as well (Butler, Galle, & Kerns, 2019), and many varieties have been developed specifically for recreational turf (Karcher, Richardson, Hignight, & Rush, 2008). One of the key characteristics of this forage is its association with a mutualistic fungal endophyte, Epichloe coenophiala , which renders the plant moderately toxic to herbivores with production of ergot alkaloids during peak growth periods in spring and fall (Stuedemann & Hoveland, 1988).…”
Section: Introductionmentioning
confidence: 99%